Educating innovative and critical thinking managers - Martínez-Hague, Paloma (2017)
Critical thinking is recognized as a competency for life, as a basic component of creativity and innovation; and as a key professional expertise for organizations worldwide. The aim of this paper is to propose different ways of teaching critical thinking to future managers in order to prepare them for challenging organizational situations that must be confronted in an innovative and critical way. This is achieved by sharing research results and tools for management education.